Mental Health in Afghanistan (Salam International Academic Journal, 2011)
Whilst the war in Afghanistan continues, there has been an obvious challenge tothe acute medical services to necessarily priorities the demands of on-going illnessand injury. In focusing on this, little attention has been given to the effects of the waron mental health. This brief paper aims to highlight the extent of mental illness inAfghanistan, identifying the most common problems and makes reference to strategicconsiderations for developing services.
Keywords: Mental Health; Afghanistan; War; mental illness